Enumeration of Mycobacterium leprae using real-time PCR. - Richard W Truman; P Kyle Andrews; Naoko Y Robbins; Linda B Adams; James L Krahenbuhl; Thomas P Gillis (Public Library of Science (PLoS), 2008)
Mycobacterium leprae is not cultivable in axenic media, and direct microscopic enumeration of the bacilli is complex, labor intensive, and suffers from limited sensitivity and specificity. We have developed a real-time PCR assay for quantifying M. leprae DNA in biological samples. Primers were identified to amplify a shared region of the multicopy repeat sequence (RLEP) specific to M. leprae and tested for sensitivity and specificity in the TaqMan format. The assay was specific for M. leprae and able to detect 10 fg of purified M. leprae DNA, or approximately 300 bacteria in infected tissues. We used the RLEP TaqMan PCR to assess the short and long-term growth results of M. leprae in foot pad tissues obtained from conventional mice, a gene knock-out mouse strain, athymic nude mice, as well as from reticuloendothelial tissues of M. leprae-infected nine-banded armadillos. We found excellent correlative results between estimates from RLEP TaqMan PCR and direct microscopic counting (combined r = 0.98). The RLEP TaqMan PCR permitted rapid analysis of batch samples with high reproducibility and is especially valuable for detection of low numbers of bacilli. Molecular enumeration is a rapid, objective and highly reproducible means to estimate the numbers of M. leprae in tissues, and application of the technique can facilitate work with this agent in many laboratories.